Oestrus Synchronization in Merino Sheep Using Intravaginal Sponges, Estrumate PMSG on Oestrus Activity - Lebata, Posane Slyvester; Dawuda , Philip Makama; Molapo , Setsumi (The Indian Journal of Animal Reproduction, 2024)
A study was conducted with 204 Merino ewes as experimental units to assess the effectiveness of four estrus synchronization protocols. The ewes were divided into four groups: TRT A (Control), TRT B (Intravaginal sponges for 14 days), TRT C (Double prostaglandin injections on days 0 and 11) and TRT D (Intravaginal sponges for 14 days, a single prostaglandin injection on day 12, plus PMSG). Six rams were used to detect heat, with standing to be mounted as the primary indicator of estrus. There were no significant differences (p>0.05) in estrus response rates among the groups: 94.10% for TRT B, 96.20% for TRT D, and 90.20% for both TRT A and TRT C. Additionally, the time from treatment withdrawal to the onset and end of estrus showed no significant variation (p>0.05). The duration of estrus differed significantly among the treatments (TRT D, TRT A, and TRT C) with notable differences at specific time intervals: 48h and 36h for TRT D, and 24h for TRT C (p
Keywords: Estrus; Progesterone; Prostaglandin; PMSG; Synchronization